Studi Komparatif Pelaksanaan Peradilan Pidana Islam di Negara Republik Arab Mesir dan Negara Republik Indonesia (Provinsi Nanggroe Aceh Darussalam) - Rahmadiana, Annisa (Morality: Jurnal Ilmu Hukum; Vol 7 No 2 (2021): Morality :Jurnal Ilmu HukumDO - 10.52947/morality.v7i2.212, 2021)
Abstract: This article discusses the implementation of Islamic criminal justice in Indonesia, especially in the Province of Nanggroe Aceh Darussalam and the Arab Republic of Egypt. Between Egypt and Indonesia have the same reference in the implementation of Islamic law in the judiciary, namely referring to the Qur'an and Hadith. The Aceh Syar'iyah Court has a position as part of a special judicial institution under the auspices of the general court and the religious court according to the type of case being handled. Meanwhile, the Court in Egypt has a wider scope with each function and authority according to its level. The research method used in the preparation of this article is a comparative study by comparing the similarities and differences inherent in Indonesia and Egypt in terms of the implementation of Islamic law which is studied through reading materials, including books, laws and regulations, and various other related sources.   Keywords : Court, Judiciary, Islamic Law, Aceh, Egypt